Technology in dementia care - CAHILL, SUZANNE (IOS Press, 2007)
The aim of this paper is to provide a clinical overview of Alzheimer's disease and the related dementias and to detail the progressive losses ? physical, social and psychological ? experienced by the individual diagnosed and the implications such losses have for user requirements in assistive technologies. The paper argues that in the absence of a cure for Alzheimer's disease and the related dementias, more innovative social care policies will need to be developed, designed to address the unique and complex needs of all those diagnosed. Although, assistive technologies have much potential in helping to compensate for the multiple losses experienced by those diagnosed it is argued that their potential has not been fully realised. The paper opens with a discussion of when Alzheimer's disease was first clinically identified, and identifies reasons behind the present increase in numbers of people presenting with this disability across the world. A brief description of the clinical symptoms of the most common dementias is provided and of how the disease can adversely affect the daily living of people affected. Examples are given on how technology can support people with dementia and their caregivers and what requirements should be considered regarding their function and design.
PUBLISHED
Keywords: Health care sciences and services; Assistive technology; Alzheimer's disease